Gait Phase Detection for Normal and Abnormal Gaits Using IMU - Han, Yi Chiew; Wong, Kiing Ing; Murray, Iain (2019)
© 2001-2012 IEEE. Gait phase detection is essential for clinicians to examine the gait cycles of human test subjects. In this paper, a method to detect normal and abnormal gait phases using a single inertial measurement unit attached to the shank is proposed. The local maxima, minima, and zero crossings of the shank's angular velocity and acceleration are used to detect heel strike, toe strike, and toe off. The proposed method may provide human-understandable insights into the shank's angular velocity and acceleration to assist clinicians to evaluate the patients' gaits. The proposed method is compared with an existing method that uses force sensitive resistors placed under the foot. The mean absolute sample difference between the proposed and existing methods is low at around 2 sample difference, equivalent to 20 ms difference.